Analysis of Information Technology Governance Implementation in Consulting Firms Using the COBIT Framework Approach: A Literature Review - Mirza, Arvin Muhammad; Wirani, Yekti; Sucahyo, Yudho Giri (Sebatik, 2025)
Information Technology (IT) governance is a critical element in supporting the achievement of an organization’s or company’s strategic objectives and ensuring the effective and efficient utilization of IT resources. Consulting firms, as the entities that prioritize delivering optimal services to their clients or partners, require a structured and well-implemented IT governance to support improvements in their business service quality. The effectiveness of IT governance implementation can be more accurately measured through the use of internationally recognized standard frameworks, such as the COBIT framework. This study aims to analyze existing literature that discusses the implementation of IT governance in consulting firms using the COBIT framework approach. This study is conducted through a literature review of relevant academic publications. The findings of this study are expected to contribute to a deeper understanding of IT governance practices in the consulting service sector and serve as a reference for the development of more effective strategies to strengthen IT governance implementation.